FENOMENA POLISEMIK BAHASA ARAB DALAM AL-QUR’AN DAN IMPLIKASI PEMBELAJARANNYA - Hamdani, Wagino Hamid; Abdurrahman, Maman (Universitas Pendidikan Indonesia, 2014)
This study aims to reveal the Arabic polysemy in the Koran and its variation of lexico-grammatical meaning. Ten forms of polysemy were obtained, namely, (ÙÙŽØ¹ÙŠÙ„), (ÙÙØ¹Ø§Ù„), (ÙÙŽØ¹Ù’Ù„Ø§Ù† ÙÙØ¹Ù’Ù„Ø§Ù† - ÙÙØ¹Ù’Ù„Ø§Ù†), (ÙÙØ¹ÙÙ„),(ÙÙŽØ¹ÙŽÙ„ÙŽØ©), (ÙÙØ¹ÙÙˆÙ’Ù„), (ØªÙØ¹Ù‘ÙŽÙ„), (ØªÙÙŽØ¹Ù‘Ù„ÙÙˆØ§), (Ø£ÙÙ’Ø¹ÙŽÙ„), and (ÙÙŽØ¹ÙŽÙ„). Each contains four morphological meanings, three morphological meanings, four morphological meanings, three morphological meanings, five morphological meanings, three morphological meanings, two morphological meanings, four morphological meanings, four morphological meanings, and five morphological meanings, respectively. The appearance of the Arabic polysemy in the Koran is attributed to (i) the process associated with the application of morphophonemic hadzf, ta mudhara'ah, (ii) the morphological process which includes morf, morfem, tauziâ€™ sharfy, and tahlil dakhili lil kalimah, and (iii) the morphosyntactic process which includes tauzi' sharfy-tarkiby, tarkib idhafi, and tarkib 'adadi. In general (61.38%), the Arabic polysemic forms in the Koran have lexico-grammatical variations including repetitive (33.83%), synonyms (11.11%), polisemic (6.80%), and grammatical (9,50). In addition, there are two polysemic forms, namely: (ÙØ¹Ù’Ù„Ø§Ù†) and (ÙØ¹ÙŽÙ„Ø©) which have a lexical-grammatical variety in the high category (77.78%) and (72.00%), the other four (4) polisemic Arabic forms, namely:Â (Ø£ÙØ¹Ù„ÙŽ) (ÙØ¹ÙÙŠÙ„), (ÙØ¹ÙŽÙ„), and (ÙØ¹ÙÙˆÙ„) have high levels of lexico-grammatical variation in the medium category: (63.81%), (66.04 %), (68.52%) and (69.87%), respectively.